REDUCTIVE TRANSFORMATION OF IRON AND SULFUR IN SCHWERTMANNITE-RICH ACCUMULATIONS ASSOCIATED WITH ACIDIFIED COASTAL LOWLANDS - Burton E.D.; Bush R.T.; Sullivan L.A.; Mitchell D.R.G. (My University, 2007)
We examined the transformations of Fe and S associated with schwertmannite (Fe8O8(OH)6SO4) reduction in acidified coastal lowlands. This was achieved by conducting a 91 day diffusive-flux column experiment, which involved waterlogging of natural schwertmannite- and organic-rich soil material. This experiment was complemented by short-term batch experiments utilizing synthetic schwertmannite. Waterlogging readily induced bacterial reduction of schwertmannite-derived Fe(III), producing abundant pore-water FeII, SO4 and alkalinity. Production of alkalinity increased pH from pH 3.4 to pH ~6.5 within the initial 14 days, facilitating the precipitation of siderite (FeCO3). Interactions between schwertmannite and FeII at pH ~6.5 were found, for the first time, to catalyse the transformation of schwertmannite to goethite (αFeOOH). Thermodynamic calculations indicate that this FeII-catalysed transformation shifted the biogeochemical regime from an initial dominance of Fe(III)-reduction to a subsequent co-occurrence of both Fe(III)- and SO4-reduction. This lead firstly to the formation of elemental S via H2S oxidation by goethite, and later also to formation of nanoparticulate mackinawite (FeS) via H2S precipitation with FeII. Pyrite (FeS2) was a quantitatively insignificant product of reductive Fe and S mineralization. This study provides important new insights into Fe and S geochemistry in settings where schwertmannite is subjected to reducing conditions. © 2007 Elsevier Ltd. All rights reserved.
Keywords: schwertmannite